1977
DOI: 10.1007/bf01053437
|View full text |Cite
|
Sign up to set email alerts
|

Juridic decisions: In ignorance of the law or in light of it?

Abstract: Pattern jury instructions have been criticized for being less than understandable to the average juror and thus for causing arbitrary juridic decisions. Two studies were conducted to establish whether these criticisms are justified and to find solutions to these problems. Both studies established the validity of the criticisms by demonstrating that the presentation of presently used Michigan negligence instructions is about as effective in helping jurors understand the laws as the presentation of no instructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
134
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 72 publications
1
134
0
Order By: Relevance
“…Thus, although the main effect of instructions was the same for both samples (as in Elwork et al, 1977), the instructions' effect did vary across samples when combined with the variable of the judge's belief. There are three reasons not to be overly concerned by this fi nding: First, the sample size in Halverson et al's (1997) second experiment (10-14 per cell) is much smaller than in their fi rst experiment (30 per cell), making the results of the second experiment potentially less stable.…”
Section: Experimental Replicationsmentioning
confidence: 98%
“…Thus, although the main effect of instructions was the same for both samples (as in Elwork et al, 1977), the instructions' effect did vary across samples when combined with the variable of the judge's belief. There are three reasons not to be overly concerned by this fi nding: First, the sample size in Halverson et al's (1997) second experiment (10-14 per cell) is much smaller than in their fi rst experiment (30 per cell), making the results of the second experiment potentially less stable.…”
Section: Experimental Replicationsmentioning
confidence: 98%
“…Elwork, Sales, and Alfini (1977) found that mock jurors instructed prior to trial were more likely to favor a defense interpretation on two of three disputed issues in an automobile negligence case. However, it is not 1 It is possible that jurors acquire some familiarity with the law prior to the judge's instructions.…”
Section: Jurors' Information Processingmentioning
confidence: 98%
“…Early research in this area demonstrated that the use of psycholinguistic principles to rewrite instructions improved juror comprehension (e.g., Elwork, Sales, & Alfini, 1977), but it has been noted that there has been limited research since then (e.g., Finkel, 2002), potentially because it was perceived by practitioners that jurors did not have a problem with comprehending instructions (Ellsworth & Reifman, 2000; although see Marder, 2006 andAmerican Bar Association, 2005 for notable exceptions). Research has consistently shown that this is not the case (e.g., Ellsworth, 1989).…”
Section: Comprehension Of Instructionsmentioning
confidence: 99%